Economic and environmental assessment of solar air-conditioning systems in Morocco. (October 2015) - Allouhi, Amine; Kousksou, Tarik; Jamil, Abdelmajid; El Rhafiki, Tarik; Mourad, Youssef; Zeraouli, Youssef
Abstract: In addition to their harmful impact on the environment, air-conditioning applications account for a significant percentage of total energy utilization; thinking about clean resources becomes a world priority. Solar cooling systems using either adsorption or absorption technologies show a great potential since they can use a permanent energy and operate with environmentally safe working pairs. This paper investigates the potential of solar air-conditioning systems in Morocco (enjoying different climates) through a comparative study between conventional and solar closed cycle processes based on economic and environmental indicators. Accordingly, annual simulations in 6 climatic zones were performed to estimate cooling loads for a typical Modern Moroccan House. The major finding of this work is that solar air-conditioning systems in hot climates must be an attractive alternative to mitigate CO2 emissions and increase energy savings. However, the high installation cost is a main obstacle facing their implementation.